Incidence and Risk of Fatal Vehicle Crashes Among Professional Drivers: A Population-Based Study in Taiwan - Tsai, Jui-Hsiu; Yang, Ya-Hui; Ho, Pei-Shan; Wu, Trong-Neng; Guo, Yue Leon; Chen, Pau-Chung; Chuang, Hung-Yi (Frontiers in Public Health, 2022)
Fatal vehicle accidents (FVAs) are among the leading causes of death worldwide. Professional drivers often drive under dangerous conditions; however, knowledge of the risk factors for FVAs among professional drivers remain scant. We investigated whether professional drivers have a higher risk of FVAs than nonprofessionals and sought to clarify potential risk factors for FVAs among professional drivers. We analyzed nationwide incidence rates of FVAs as preliminary data. Furthermore, by using these data, we created a 1:4 professionals/nonprofessionals preliminary study to evaluate the risk factors. In Taiwan, the average crude incidence rate of FVAs for 2003–2016 among professional drivers was 0.92 per 1000 person-years; professionals had a higher percentage of FVAs than nonprofessionals among all motor vehicle accidents. In the 14-year preliminary study with frequency-matched nonprofessionals, the risk of FVAs among professionals was significantly associated with a previous history of involvement in motor vehicle accidents, previous history of benzodiazepine use, and speeding. The findings have value to policymakers seeking to curtail FVAs.